Efektifitas Penggunaan Media Kartu Bilangan Pada Materi Operasi Bilangan Untuk Meningkatkan Motivasi Belajar - Febby Noorlyanna Zhakilla (RANGE: Jurnal Pendidikan Matematika, 2023)
This study aims to see the effectiveness of using number cards in integer operations to increase learning motivation at SMP Negeri 1 Purwaanegara. This type of research is classroom action research (CAR) using the LAPS-Heuristic learning model. The number of subjects in this study were 64 students, to obtain data in this study the researchers collected data by giving tests, interviews and questionnaires. For the use of the subject in each data collection technique, it will be different where for filling out the questionnaire using all subjects, namely 64 students and for the interview the researcher uses as many as 9 students as the subject where the researcher chooses the subject based on the high level of 3 students, low 3 students and medium 3 students. This research consists of two cycles, cycle I and cycle II, where each cycle will consist of 2 meetings. Based on the two cycles, it will be seen how the development of students' learning motivation towards the integer operations material in each cycle that has been carried out. Thus the results show that there is an increase in students' learning motivation after using integer cards which is indicated by the results of 75,14%. Keywords: Motivation, Number Card, Number Operation